2020
DOI: 10.1016/j.eclinm.2020.100591
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes among hospitalized adults with severe COVID-19 admitted to a tertiary medical center and receiving antiviral, antimalarials, glucocorticoids, or immunomodulation with tocilizumab or cyclosporine: A retrospective observational study (COQUIMA cohort)

Abstract: Background The COVID-19 outbreak challenges the Spanish health system since March 2020. Some available therapies (antimalarials, antivirals, biological agents) were grounded on clinical case observations or basic science data. The aim of this study is to describe the characteristics and impact of different therapies on clinical outcomes in a cohort of severe COVID-19 patients. Methods In this retrospective, single-center, observational study, we collected sequential dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 54 publications
7
66
1
6
Order By: Relevance
“…In addition, we identified 10 additional cohort studies since our first review 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 . A total of 28 cohort studies, at moderate risk of bias, reported on adjusted effect estimates of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we identified 10 additional cohort studies since our first review 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 . A total of 28 cohort studies, at moderate risk of bias, reported on adjusted effect estimates of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Excitingly, prospective trials using cyclosporin A have recently begun (ClinicalTrials.gov: NCT04412785). A retrospective observational study recently found that in hospitalized patients, among the prescribed therapies, including lopinavir/ritonavir and hydroxychloroquine, only cyclosporine was significantly associated with a decrease in mortality (Guisado-Vasco et al, 2020). Perhaps the combined activity of immunosuppression and antiviral activity led to these promising results.…”
Section: Discussionmentioning
confidence: 99%
“…The second subgroup was composed of studies that evaluated hospitalized COVID-19 patients who recovered or died (39,722 died and 295,500 recovered) (Chen et al, 2020b;Chen et al, 2020c;Chen et al, 2020d;Deng et al, 2020;Guisado-Vasco et al, 2020;Javanian et al, 2020;Li et al, 2020c;Morrison et al, 2020;Ñamendys-Silva et al, 2020;Parra-Bracamonte et al, 2020;Shang et al, 2020;Vena et al, 2020;Yao et al, 2020;. The characteristics of the studies included in the meta-analysis are shown in Tables 1A and 1B.…”
Section: Search Resultsmentioning
confidence: 99%